The ambiguous gifts o f Afrodite (Iter, 2022)
Can Greek concept of Beauty inelude dece i t and death? To answer this question. the authoranalices some aspeets of Afrodite s myth and Pandora 's myth. Both myths shows the relationbetween Beauty. pie asure, death and deceit. Finally the text asserts that like a mirror thehuman body. young and beautiful human body. reflects the shine of divine Beauty. even itsambiguity shine-dark. life-death. pleasure-hurt.
Keywords: Beauty. Ambiguity. Deceit. Body. Mirror